Artistic and Aesthetic Specifics of Using the Piano in the Acoustic Space of Joe Hisaishi Film Music - Zaytseva, Marina; Titova, Tatiana (Traektorii͡a︡ nauki : mezhdunarodnyĭ ėlektronnyĭ nauchnyĭ zhurnal, 2016)
The article explains the problems of music functioning in the media text system, analyzes the stages of the creative collaboration of composer Joe Hisaishi and director Hayao Miyazaki in the creation of animated films, highlights the most important events in the biography of artists. On the example of the animated film "Spirited Away" (2001), the peculiarities of interaction of music, voice and video in the series are revealed, the role of the piano in the acoustic space of film music by Joe Hisaishi is defined. В статье обосновывается проблематика функционирования музыки в системе медиатекста, анализируются этапы творческого сотрудничества композитора Джо Хисаиши и режиссера Хаяо Миядзаки в процессе создания анимационных фильмов, освещаются важнейшие события  биографии этих мастеров. На примере анимационного фильма «Унесенные призраками» (2001) выявлены особенности взаимодействия музыкального, речевого и видео рядов в определена роль фортепиано в акустическом пространстве киномузыки Джо Хисаиши.